Introducing spring framework : a primer - Gutierrez, Felipe (Apress, 2014)
Introducing Spring Framework is your hands-on guide to learning to build applications using the Spring Framework. The book uses a simple My Documents application that you will develop incrementally over the course of the book and covers: • How to programmatically configure the Spring container and beans • How to use annotations for dependency injection • How to use collections and custom types • How to customize and configure bean properties and bean lifecycle interfaces • How to handle metadata using XML, annotations, and the Groovy bean reader • How to use the new Spring Boot and Spring XD After reading this book, you will have all you need to start using the Spring Framework effectively.